Trends in the use of antipsychotics in the Israeli inpatient population, 2004–2013. Issue 1 (December 2016) - Ponizovsky, Alexander; Marom, Eli; Ben-Laish, Michal; Barash, Igor; Weizman, Abraham; Schwartzberg, Eyal
Abstract Background Although serious mental illneses are treated with both typical and atypical antipsychotic grugs, trends in their use in psychiatric inpatient population in Israel are unrecognized. The aim of this study was to detect trends in the use of typical and atypical antipsychotic drugs in the Israeli inpatient psychiatric population throughout the last decade. Methods Data regarding allocation of typical and atypical antipsychotics, over the period 2004 to 2013, were extracted from the electronic records of SAREL, Israel's largest private supplier of drugs to healthcare and medical facilities. The data were converted to defined daily doses (DDD) per 1000 inpatients per day. Results Usage of the ten atypical antipsychotic agents allocated through Israel's national health care system increased by 73 %, from 128.09 DDD/1000 inpatients/day in 2004 to 221.69 DDD/1000 inpatients/day in 2013. This rise from 2004 to 2013 was largely due to a 1.6-fold increase in the administration of olanzapine (48.31 to 79.57 DDD/1000 inpatients/day), a 4.4-fold increase of quetiapine (9.74 to 43.04 DDD/1000 inpatients/day) and 3.7-fold increase of amisulpride (5.54 to 20.38 DDD/1000 inpatients/day). At the same period, the total utilization of 12 main typical antipsychotics decreased by 15.5 %, from 148.67 DDD/1000 inpatients/day in 2004 to 125.57 DDD/1000 inpatients/day in 2013. Over the entire period, total DDDs of both classes of antipsychotics (typical and atypical) increased by 38 %. Conclusions Similar to trends in the treatment of psychiatric outpatients in other countries, there was a substantial increase in the administration of atypical antipsychotic drugs to the Israeli psychiatric inpatient population across the study period. A decrease in the use of typical antipsychotics (substitution), polypharmacy, administration for more indications (supplementation) and the use of larger doses of antipsychotics may account, in part, for this increase. The findings have implications for mental health policy in the context of the Mental Health Care System Reform. Systematic studies on appropriate dosing of antipsychotics and augmentation strategies are warranted.